Cardiorespiratory responses and circulating metabolite concentrations in male and female adolescents during a simulated duathlon - Naughton, G. A.; Carlson, J. S.; Iuliano, S.; Gibbs, M.; Snow, R. J. (International Journal of Sports Medicine, 1998)
This study compared markers of the metabolic processes occurring in male and female adolescent triathletes from two age groups (over 15 years of age [O15] and under 15 years of age [U15]) during a laboratory based duathlon. Participants were tested on three separate occasions; two peak VO2 tests on a treadmill and cycle ergometer, and a third session involved a simulated duathlon (2 km run, 12 km ride and 4 km run for the O15 group or 1 km run, 8 km ride and 2 km run for the U15). Data collection included performance speed, cardiorespiratory responses and blood borne markers of exercise metabolism. The performance speeds selected by the two age groups did not differ. The mean relative percentage of VO2peak at which subjects participated were 79+/-3, 77+/-4%, for the O15 males and females, and 71+/-5 and 82+/-2%, for the U15 males and females, respectively. While the plasma metabolites of ammonia [NH3] and lactate [La] were not different between age groups and sex (p>0.05) there were however, higher concentrations recorded during the cycling phase when compared with the running phases (p < 0.05). The respective mean concentrations for NH3 and La were 80.5+/-5.6 microM, and 4.9+/-0.3 microM for cycling, and 56.3+/-2.7 microM, and 2.7+/-0.2 microM for the combined running phases.